(untitled) (Research, Society and Development, 2020)
The cultivation of soy is gaining more and more importance in Brazilian and global agriculture. The use of oilseeds is diverse and the area of cultivation of the crop has been increasing annually due to the growth in global demand. Accompanied by this increase in cultivation, the use of more efficient and heavier machines leads to soil compaction, affecting the development of roots. The objective of this work will be to evaluate the development of soybean plants in compacted areas with the application of plant growth regulator, Stimulate®. The experiment will be conducted in an experimental area with soil classified as a typical Latossolo Vermelho Distrófico, on a sandy texture located at the State University of Maringá - UEM - Umuarama-PR Campus. At the highest levels of traffic, the growth regulator was not able to overcome the damage from excessive traffic and with the increase in the level of traffic there is also an increase in the resistance of the soil to penetration in depth.